Advanced Surface Characterization Techniques in Nano- and Biomaterials - Gutierrez-Ceron, C; Gutierrez-Ceron, C (Springer International Publishing, 2019)
​Although metallic nanoparticles have been applied in various fields of biomedical engineering research for quite some time, generating new biomaterials with improved regenerative capabilities remains the cornerstone in tissue engineering and regenerative medicine. These materials, once implanted in patients, will ultimately be invaded by endogenous cells, which emphasizes the relevance of surface composition as a critical factor in determining the regenerative potency of a given material. In this chapter, we present a brief revision on fundamental concepts and an up-to-date overview for surface characterization of nano-engineered structures. © Springer Nature Switzerland AG 2019.